INCREASING CHILDREN'S CONFIDENCE THROUGH STIMULUS METHODS AND DEMONSTRATION METHODS IN DANCE LEARNING AT SANGGAR PURI RANGGPATI TANGERANG BANTEN - Putri Asih Julianti; Elindra Yetti; Kartika Mutiara Sari (Journal of Dance and Dance Education Studies, 2023)
This study aims to 1) describe the application of stimulus methods and demonstration methods in dance learning to improve the child's confidence in Sanggar Puri Rakumatati Tangerang, 2) improve the child's confidence through stimulus methods and demonstration methods in dance learning in Sanggar Puri Rakumatati Tangerang. The study used class action research methods and Kurt Lewin's action research design. Data collection techniques use observations and field record methods with qualitative data analysis techniques descriptions and statistical quantifications. The study was conducted on 10 children aged 4 to 6 at the Puri Ranggatati Studio, Tangerang, Banten. Triangulation techniques use triangulation methods, theories, and time. The results of this study show increased confidence in children. The pre-cycle assessment received an average value (34.45), the I cycle received an average value (64.6) and the II cycle received an average value (91.95). The use of stimulus methods and demonstration methods gives a positive change to the child's behavior, and gift giving can give the child motivation to strengthen their confident behavior. The confidence of the child in the respiratory tract can be improved through stimulus methods and demonstration methods seen from the increase in pre-cycle, cycle I, and cycle II scores. The coach should be able to find and apply the right dance learning methods for children.